The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.12816/0003345
|View full text |Cite
|
Sign up to set email alerts
|

Is a Team-based Learning Approach to Anatomy Teaching Superior to Didactic Lecturing ? = هل نهج طريقة التعلم القائم على الفريق لعلم التشريح أفضل من إلقاء المحاضرات التعليمية ؟

Abstract: Objectives:Team-based learning (TBL) is used in the medical field to implement interactive learning in small groups. The learning of anatomy and its subsequent application requires the students to recall a great deal of factual content. The aims of this study were to evaluate the students' satisfaction, engagement and knowledge gain in anatomy through the medium of TBL in comparison to the traditional lecture method. Methods: This study, carried out from February to June 2012, included 30 physical therapy stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 17 publications
(35 reference statements)
1
5
0
Order By: Relevance
“…Extending the previous findings on the effectiveness of implementing TBL approach in improving PT students’ academic outcomes in gross anatomy courses [ 4 - 6 ], results of this study provided evidence to support the use of the TBL approach to increase students’ exam scores when compared to the traditional instructional method in two PT patient/client management courses. The effect sizes of the TBL approach on both courses were comparable, which are considered a medium effect.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Extending the previous findings on the effectiveness of implementing TBL approach in improving PT students’ academic outcomes in gross anatomy courses [ 4 - 6 ], results of this study provided evidence to support the use of the TBL approach to increase students’ exam scores when compared to the traditional instructional method in two PT patient/client management courses. The effect sizes of the TBL approach on both courses were comparable, which are considered a medium effect.…”
Section: Discussionsupporting
confidence: 74%
“…The increase in exam scores in DPT students taught using the TBL approach may be due to the following reasons. First, DPT students’ perceptions and satisfaction toward TBL have been reported to be favorable by other investigators [ 4 - 6 ], perhaps increasing stu dents’ engagement and interest in course content and therefore enhancing their learning. Second, several investigators reported students’ improved problem solving and increased knowledge retention when TBL approach was used [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, during phase 3 (application exercise) it was notable that some students' unwilling to challenge colleagues, lack confidence to voice their ideas or opinions to the class and educator, and anxious during presentation though it was not part of the module summative assessment. A plausible reason might be as the task design was matched to real-life scenarios, it might have challenged some student's coping skills to demands on accountability, working in teams, being creative, and time management skills (Atwa et al, 2019;Ghorbani et al, 2014;Livingston et al, 2014).…”
Section: Challengesmentioning
confidence: 99%
“…Studies have shown that interactive small-group discussion, simulation, and deliberate practice are more effective than didactic large-group teaching. [4][5][6] Furthermore, simulation-based teaching has been shown to be more effective at preparing junior doctors for assessment and management of critically ill patients when applied to related disciplines, such as trauma, 7 emergency medicine, 8 and ENT emergencies. 9 This article describes the teaching program designed by CUWMS and offers an example of a low-cost, easy-toimplement course as an adjunct to an already crowded undergraduate medical education.…”
Section: Introductionmentioning
confidence: 99%